A Note on Halal Sustainable Tourism - Uula, Mimma Maripatul (Halal Tourism and Pilgrimage, 2024)
This study aims to see the development of research on the topic "Halal Sustainable Tourism" and research plans that can be done based on journals published on the theme. This research uses a qualitative method with a bibliometric analysis approach. The data used is secondary data with the theme "Halal Sustainable Tourism" which comes from the Dimension database with a total of 174 journal articles. Then, the data is processed and analyzed using the VosViewer application with the aim of knowing the bibliometric map of "Halal Sustainable Tourism" research development in the world. The results of the study found that there were 4 clusters with the most used words being halal tourism, tourism, Indonesia, concept, tourist, destination, value, service, business, impact, intention, and community. Then, the topics of research lines related to Halal Sustainable Tourism are Sustainable Halal Tourism Development, Impact of Halal Tourism on the Environment, Technology in Halal Tourism Development, and Halal Tourism and Sustainable Development.